Project Team Cohesion: When Goals Matter Less Than Intrapreueurship - Alves, Alberto; Santino Bizarrias, Flavio; Scafuto, Isabel Cristina; Penha, Renato; Silva, Luciano Ferreira da (Revista Administração em Diálogo - RAD, 2025)
Agile projects demand self-managed teams with enough cohesion to meet the established objectives. We propose pioneering that project teams may have the necessary levers for their strengthening in intrapreneurship and goal orientation. In this sense, this study aims to evaluate the influence of an individual’s intrapreneurship and goal orientation on team cohesion, mediated by agility in projects. A systematic literature review was conducted to provide theoretical support for the study, supplemented by structural equation modeling and mediation analysis for the conditional tests. The results suggest a more significant influence of intrapreneurship on team cohesion than goal orientation in agile contexts.